To simplify the equation 3 square root 8^1/4x, we can utilize the properties of exponents and roots. This converts the expression to 3 * 8^1/8x.
The original expression in question is 3 square root of 8 raised to the power of 1/4x. We can begin to simplify this expression by first recognizing the properties of exponents. For example, the calculation of 8 raised to the 1/4 power represents the same as taking the fourth root of 8. Furthermore, the square root of a number is the same as raising that number to the power of 1/2.
So, 3 square root (8^1/4x) can be written as 3 * (8^1/4x)^1/2, which simplifies to 3 * 8^1/8x, due to the property that multiply exponents when raising powers to a power. Using properties of exponents helps us in simplifying complex equations.
#SPJ11
The temperature change is: 12°F
The temperature change from 6 a.m. to 11 a.m. can be calculated by subtracting the initial temperature from the final temperature.
In this case, the initial temperature at 6 a.m. was -12°F and the final temperature at 11 a.m. was 0°F.
Therefore, the temperature change is 0°F - (-12°F) = 12°F. So, the correct answer is C) 12
Read more about Temperature Change at: brainly.com/question/25677592
#SPJ2
Complete question is:
The temperature at 6 a.m. was −12°F. At 11 a.m. the temperature was 0°F. Which of the following shows the temperature change from 6 a.m. to 11 am?
A −12
B 0
C 12
D 24
Answer:
+12 degrees
Step-by-step explanation:
You never showed a picture, but im pretty sure this is correct
I hope this helped, please mark Brainliest, thank you!
Answer:the last one
Step-by-step explanation:
Answer: g(x) = (x + 1)² + 3
Step-by-step explanation:
The vertex form of a quadratic equation is: y = a(x - h)² + k where
f(x) = x²
Given: 3 units up --> k = 3
1 unit left --> h = -1
g(x) = (x + 1)² + 3
The translation of the graph of a function is one where the graph is moved to a different location on the plane that does not include a change in shape or rotation
The resulting function from the translation of the function f(x) = x², 3 units up and 1 unit left, g(x) = x² + 2·x + 4
The process by which the above value for g(x) is found is presented as follows:
The given function f(x) = x²
The vertical translation given to the function = 3 units up
The horizontal translation given to the function = 1 unit left
The required parameter;
To find the resulting function g(x) that has results from the given translations
Solution:
A translation of a function y = f(x) vertically,k units upwards is the function y = f(x) + k
A translation of a function y = f(x) horizontally, k, units left, is the function y = f(x + k)
Therefore, we get
g(x) = f(x + 1) + 3 = (x + 1)² + 3 = x² + 2·x + 4
g(x) = x² + 2·x + 4
Learn more about translation of functions here:
Answer:
B -3.
Step-by-step explanation:
The slope = (y2-y1)/(x2-x1)
= (-2-4)/(8-6)
= -6/2
= -3.
Answer:
yeah i think so